STRAIN GAUGE TESTING OF 3D-PRINTED CFRP SANDWICH STRUCTURE: Received: 02nd August 2023 Revised: 18th July 2023, 22nd December 2023, 29th December 2023, 16th January 2024, 29th January 2024 Accepted: 03rd August 2023 - Paweł Żur; Alicja Żur; Piotr Michalski; Andrzej Baier (MATTER: International Journal of Science and Technology, 2024)
In this article, the authors present composite sandwich-type CFRP structures and a study of their properties by strain gauge testing. The paper presents the modeling of a parameterized elementary unit serving as the core of a 3D printed structure using Fused Deposition Modelling (FDM) technology. The properties of these structures with different outer layers made of pure epoxy resin and resin with 10% and 20% carbon fiber powder were then investigated. Based on the results of the strain gauge tests, material models were reconstructed for each resin layer, which can be used in computer FEM studies of more complex components. As an application example, a strength analysis of the driver’s seat of a Greenpower car made with printed sandwich structures coated with carbon fiber powder resin was conducted.